Map of suitability for the spontaneous growth of Tuber magnatum in Emilia-Romagna (Italy) - Nicola Laruccia (Italian Journal of Mycology, 2020)
In this work we used an inductive and deductive approach to produce the map of suitability for the spontaneous growth of Tuber magnatum (white truffle) (SSGT) in Emilia-Romagna region (northern Italy). This map was produced in order to identify the environments where appropriate actions should be applied to protect this threatened truffle species.The steps used to define the map were: 1) surveying and mapping the actual productive areas (APAs) in two provinces of Emilia-Romagna (Bologna and Modena); 2) identification of some morphological, climatic, vegetational and pedological properties related to T. magnatum development; 3) production of digital maps representing the value (classified) that each property assumes in discrete land portions; 4) overlapping the map of APAs with each of the thematic maps and selection of the properties showing the strongest relationships with the presence of T. magnatum; 5) creating the map of SSGT, covering the whole hilly area of Emilia Romagna region; 6) assessing the reliability of the SSGT map, by overlapping the APAs map and the areas of the provinces of Parma and Piacenza where the mycelium of T. magnatum was found using species-specific primers.The relationships found by means of the inductive approach (comparison between selected properties and observed frequency of truffle) demonstrated its effectiveness in predicting deductively the areas with distinct suitability for truffle.